2021
DOI: 10.1186/s40560-021-00566-4
|View full text |Cite
|
Sign up to set email alerts
|

The Ichikado CT score as a prognostic tool for coronavirus disease 2019 pneumonia: a retrospective cohort study

Abstract: Background The relationship between computed tomography (CT) and prognosis of patients with COVID-19 pneumonia remains unclear. We hypothesized that the Ichikado CT score, obtained in the first 24 h of hospital admission, is an independent predictor for all-cause mortality during hospitalization in patients with COVID-19 pneumonia. Methods Single-center retrospective cohort study of patients with confirmed COVID-19 pneumonia admitted at our institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
4
1
Order By: Relevance
“…GGOs on CT might reflect an increase in interstitial fluid or protein accumulation. A high extent of GGO implies diffuse alveolar involvement and correlates with higher mortality when combined with the presence of fibrotic changes [17,18,38]. In contrast to previous studies, our investigation revealed that the presence of extensive GGOs on CT (≥ 15 points), regardless of fibrotic change, led to a 4.07-fold increase in the odds of 60-day mortality.…”
Section: Discussioncontrasting
confidence: 88%
“…GGOs on CT might reflect an increase in interstitial fluid or protein accumulation. A high extent of GGO implies diffuse alveolar involvement and correlates with higher mortality when combined with the presence of fibrotic changes [17,18,38]. In contrast to previous studies, our investigation revealed that the presence of extensive GGOs on CT (≥ 15 points), regardless of fibrotic change, led to a 4.07-fold increase in the odds of 60-day mortality.…”
Section: Discussioncontrasting
confidence: 88%
“…Consistently, our patients' collapsed areas were not associated with their outcomes. Aerated areas were related to hospital stays in line with the prognostic value of CT scans in COVID-19 pneumonia [44,45,50,51]. Our results lead towards a major role of perfusion alterations in COVID-19 ARDS [14,42,49,52,53], as Shi et al [54] showed similar compliance despite a worse gas exchange, higher extravascular lung water, and pulmonary vascular permeability index in COVID-19 ARDS versus classical ARDS.…”
Section: Relationship With Clinical Outcomessupporting
confidence: 81%
“…This study considers imaging findings in conjunction with other individual characteristics of patients (clinical features and laboratory results) to predict the severity of COVID-19. Some imaging-based scores, such as the CT severity score, have been described, but their complexity requires a fully trained and experienced radiologist to interpret the images and calculate the score; these requirements may hinder the universal application of these scores [ 21 , 22 ]. In keeping with most of the published data to date [ 8 , 9 ], in our study, age ≥ 60 years was correlated to increased mortality and ICU admission.…”
Section: Discussionmentioning
confidence: 99%